Jesus the Jew, the Mystery of Christ, and Jewish-Christian Relations - Pollefeyt, Didier (Studies in Christian-Jewish Relations, 2026)
This article addresses the central christological paradox in contemporary Jewish-Christian relations: how can Christians simultaneously affirm the enduring validity of God's "never revoked covenant" with the Jewish people and maintain Christ's unique and irreplaceable role in salvation history? Reviewing the major theological approaches developed since Nostra Aetate (1965)—including fulfillment theology as articulated by Cardinal Ratzinger, the eschatological solution proposed by theologians like Jürgen Moltmann, Logos Christology, and the recent concept of Christ as the Living Torah, the article demonstrates that each approach, despite its merits, inevitably slides into some form of supersessionism, whether explicit or deferred to the eschaton. Also Benedict XVI's later critique of the "never revoked covenant" formula reveals the persistent tensions within Catholic teaching on Judaism. As a novel and complementary alternative, the essay proposes "negative Christology," an application of apophatic theology to christological reflection. Drawing on shared Jewish and Christian traditions of divine ineffability—from Maimonides and Kabbalistic mysticism to Pseudo-Dionysius and Meister Eckhart—this approach emphasizes the mystery and ultimate incomprehensibility of Christ's identity beyond definitive categorization. By focusing on what cannot be definitively said about Christ rather than making exhaustive positive claims, negative Christology creates theological space for affirming both the Jewish covenant and Christian witness without requiring one tradition to negate or subsume the other. Crucially, negative Christology serves not as a replacement but as a corrective hermeneutical key for positive christological claims, fostering epistemological humility while preserving the Church's distinctive witness to Christ's uniqueness and enabling authentic interfaith dialogue grounded in mutual respect and shared reverence before divine mystery.